"Grammar Talks: Pelatihan Peningkatan Pemahaman Tata Bahasa melalui Diskusi Interaktif" - Badruddin, Dahniar; Suhrah, Suhrah; Juspaningsih, Juspaningsih (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to enhance the understanding of English grammar among members of the New Generation Club (NGC) through an interactive method. The program consists of several stages, including planning meetings, guided training, group discussions, practical simulations, and the provision of relevant reference books such as The Art of English and Grammar is Easy. The results of this training show significant improvements in participants' grammar skills, as well as increased confidence in communicating in English. The interactive discussion method applied has proven effective in deepening participants' understanding of grammar structures, while the use of reference books provides a strong foundation for continuous learning. Participants have shown progress not only in their understanding of grammar but also in their speaking and interaction skills in English. This training has made a positive contribution to the development of English language skills among New Generation Club members, and with its enjoyable and relevant approach to participants' needs, the training encourages them to continue learning and independently honing their language skills.